Diseñar un plan de beneficios de acuerdo con los nuevos modelos de calidad de vida organizacional, en una empresa del sector comercial (2017)
Taking into account the turnover of personnel that is presented in the sales area and that currently the new generations are not only motivated by money, it became necessary to investigate different models that provide a number of benefits that allow organizations to retain and attract the desired staff, these benefits generate a better quality of life for the employees. Among the benefits we have variable payments, job enrichment, recognition, flexible hours, professional development, family involvement and those benefits that by right any Colombian worker can and should enjoy when such a situation presents itself.